Effect of ultrasonic tip designs on intraradicular post removal - Anny Carine Barros Aguiar; Daniely Amorim de Meireles; André Augusto Franco Marques; Emílio Carlos Sponchiado Júnior; Angela Delfina Bitencourt Garrido; Lucas da Fonseca Roberti Garcia (Korean Academy of Conservative Dentistry, 2014)
Objectives To evaluate the effect of different ultrasonic tip designs on intraradicular post removal. Materials and Methods The crowns of forty human canine teeth were removed, and after biomechanical preparation and filling, the roots were embedded in acrylic resin blocks. The post spaces were made, and root canal molding was performed with self-cured acrylic resin. After casting (Cu-Al), the posts were cemented with zinc phosphate cement. The specimens were randomly separated into 4 groups (n = 10), as follows: G1 - no ultrasonic vibration (control); G2 - ultrasonic vibration using an elongated cylindrical-shaped and active rounded tip; G3 - ultrasonic vibration with a flattened convex and linear active tip; G4 - ultrasonic vibration with active semicircular tapered tip. Ultrasonic vibration was applied for 15 seconds on each post surface and tensile test was performed in a Universal Testing Machine (Instron 4444 - 1 mm/min). Results G4 presented the highest mean values, however, with no statistically significant difference in comparison to G3 (P > 0.05). G2 presented the lowest mean values with statistically significant difference to G3 and G4 (P < 0.05). Conclusions Ultrasonic vibration with elongated cylindrical-shaped and active rounded tip was most effective in reducing force required for intraradicular post removal.